Leaf histology of greenhouse plants, in vitro cultured and somatic embryo-derived plants of Bactris gasipaes Kunth (Acta Scientiarum. Biological Sciences, 2018)
In vitro cultures of peach palm (Bactris gasipaes Kunth) were established by somatic embryogenesis but some improvements in maturation and conversion steps are still needed. The aim of this study was to analyze morpho-anatomical differences in peach palm leaves from greenhouse cultured plants, in vitro plants developed from in vitro germinated seeds and somatic embryo-derived plants. Expanded leaves were prepared for histological analyses and scanning electron microscopy. No significant difference was found between ex vitro and in vitro cultured plants, but the somatic embryo-derived plants showed structural alterations of the leaves. The epidermal cells were elongated in shape, the mesophyll cells were thicker and the vascular bundle was not very developed.  In somatic embryo-derived leaves the cuticle was thinner than in other leaves and epicuticular wax was present but poorly deposited. In in vitro cultured plants, the deposition of epicuticular wax on the leaves was irregular while in the greenhouse plants it was regular and abundant. These alterations in somatic embryo-derived leaves could hinder the acclimatization and development of peach palm plants so it is necessary to improve the protocol for somatic embryogenesis to produce better plants.